Motor and cognitive performances of parkinsonian patients in the on and off phases of the disease. Issue 6 (June 1986) - Girotti, F; Carella, F; Grassi, M P; Soliveri, P; Marano, R; Caraceni, T
Abstract : Twenty-one Parkinsonian patients were tested in on and off phases during chronic levodopa therapy for cognitive function, affective status, and evaluation of motor performance with reaction and movement times. A worsening of mood was observed from the on to the off phase. No variation in cognitive performance was observed from the on to the off phase in spite of evident motor changes. Mood changes during on-off variations may reflect involvement of mesocortical and mesolimbic dopaminergic systems.